(3JMaI GdCHjGQ eeGgh efbhd Yf GdSGOI GdCNjGQs - (3GdOShbj , eMeO Hf eUWaj GdMSjfj GdTgGhj GdGRgQj GdfbTHfOj,J (B1167 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd eMeO Hf eUWai QCjJ GdfGS eef dGYbd dg hdG EjfGS YGcajf hefcHjf s
(3BNQgG (B:s
(3hGdCMGOjK cKjQI TgjQI ai Pdc hgPG BNQ eG MQQfGg hhLOfG eeG jJYdb HCHjGQ GdUfGYGJ hCgd GdMQa hGdOjGfGJ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B27s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3aQhSjI JjehQ (B63) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs